2005
DOI: 10.1158/0008-5472.can-05-1197
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Inhibits Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand–Induced Apoptosis by Activating Akt in Human Bladder Carcinoma Cells

Abstract: The antiapoptotic molecule galectin-3 was previously shown to regulate CD95, a member of the tumor necrosis factor (TNF) family of proteins in the apoptotic signaling pathway. Here, we question the generality of the phenomenon by studying a different member of this family of proteins [e.g., TNF-related apoptosis-inducing ligand (TRAIL), which induces apoptosis in a wide variety of cancer cells]. Overexpression of galectin-3 in J82 human bladder carcinoma cells rendered them resistant to TRAIL-induced apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 46 publications
7
101
1
2
Order By: Relevance
“…In agreement with this finding other studies reported that Gal-3 imparts resistance to apoptosis in breast, bladder and prostate cancer (Choi et al, 2004;Oka et al, 2005;Wang et al, 2010), by Bcl-2 up-regulation and inhibition of Gal-3 induced caspase-3 activity (Wang et al, 2010). Another report showed that use of Pect-MCP as a blocker of cell surface Gal-3 could induce apoptosis in prostate cancer by suppression of MAPK pathway (Yan and Katz, 2010).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In agreement with this finding other studies reported that Gal-3 imparts resistance to apoptosis in breast, bladder and prostate cancer (Choi et al, 2004;Oka et al, 2005;Wang et al, 2010), by Bcl-2 up-regulation and inhibition of Gal-3 induced caspase-3 activity (Wang et al, 2010). Another report showed that use of Pect-MCP as a blocker of cell surface Gal-3 could induce apoptosis in prostate cancer by suppression of MAPK pathway (Yan and Katz, 2010).…”
Section: Discussionsupporting
confidence: 70%
“…This characteristic is unique among galectins and may be responsible for the interest in Gal-3 as a target molecule (Elola et al, 2007).The anti-apoptotic function of Gal-3 has been well demonstrated in variety of human cancers, such as breast, bladder and prostate (Choi et al, 2004;Oka et al, 2005;Wang et al, 2010). It has been demonstrated that Gal-3 knockout in PC3 prostate cancer cells could sensitize cells to chemotherapeutic drugs (Wang et al, 2010).…”
Section: Synergistic Effects Of Pectasol-c Modified Citrus Pectin An mentioning
confidence: 99%
“…TRAIL represents a particularly promising anticancer agent because of its intrinsic selectivity toward cancer cells (18). At the same time, overactivation of intracellular antiapoptotic mechanisms has been shown to attenuate cancer cell sensitivity to TRAIL (19). Although U87MG cells are indeed resistant to TRAIL, we found that PIT-1 substantially sensitized U87MG cells to killing by TRAIL (Fig.…”
Section: Pit-1 Preferentially Reduces Viability Of Pten-deficient Glimentioning
confidence: 61%
“…On the contrary, over-expression of galectin-3 in J82 human bladder carcinoma cells rendered them resistant to TRAIL induced apoptosis, whereas phosphatidylinositol3 kinase PI3K inhibitors (wortmannin and LY 294002) blocked the protecting effect of galectin-3. High levels of constitutively active Akt were seen in the galectin-3 over-expressing J82 cells suggesting that galectin-3 involves Akt as a modulator molecule in protecting bladder carcinoma cells from TRAIL induced apoptosis (Oka et al, 2005). It is reasonable to assume that observed inconsistencies are probably due to use of different cell lines.…”
Section: Role Of Galectin-3 In Extrinsic Apoptotic Pathwaysmentioning
confidence: 99%